Macroeconomic Effects of Credit Deepening in Latin America - Carlos Carvalho; Nilda Pasca; Laura Souza; Eduardo Zilberman (Inter-American Development Bank (IDB), 2014)
This paper augments a relatively standard dynamic general equilibrium model with financial frictions in order to quantify the macroeconomic effects of the credit deepening process observed in many Latin American (LA) countries in the last decade, most notably in Brazil. In the model, a stylized banking sector intermediates credit from patient households to impatient households and firms. The key novelty of the paper, motivated by the Brazilian experience, is to model the credit constraint faced by (impatient) households as a function of future labor income. In the calibrated model, credit deepening generates only modest abovetrend growth in consumption, investment, and GDP. Since Brazil has experienced one of the most intense credit deepening processes in Latin America, it is argued that the quantitative effects for other LA economies are unlikely to be sizeable.
hdl:11319/6787
Keywords: E20; E44; E51; 330; Credit deepening; Financial frictions; Consignado credit; Payroll lending